Beyond COVID‐19 and lessons learned in the United States. Issue 1 (2nd August 2022) - Gammon, Richard; Katz, Louis M.; Strauss, Donna; Rowe, Kathleen; Menitove, Jay; Benjamin, Richard J.; Goel, Ruchika; Borge, Dayand; Reichenberg, Stefan; Smith, Roxane
Abstract: The COVID‐19 pandemic severely tested the resilience of the US blood supply with wild fluctuations in blood donation and utilisation rates as community donation opportunities ebbed and hospitals post‐poned elective surgery. Key stakeholders in transfusion services, blood centres, supply chains and manufacturers reviewed their experiences during the SARS‐CoV‐2 pandemic as well as available literature to describe successes, opportunities for improvement and lessons learned. The blood community found itself in uncharted territory responding to restriction of its access to donors (approximately 20% decrease) and some supplies; environmental adjustments to address staff and donor concerns about coronavirus transmission; and the development of a new product (COVID‐19 convalescent plasma [CCP]). In assuring that the needs of the patients were paramount, the donation process was safe, that clinicians had access to CCP, and vendor relationships aligned, the blood banking community relearned its primary focus: improving patient outcomes.